Epizootics of Streptococcus agalactiae infection in captive rays from Queensland, Australia. Issue 2 (24th August 2017) - Bowater, R O; Dennis, M M; Blyde, D; Stone, B; Barnes, A C; Delamare‐Deboutteville, J; Horton, M A; White, M; Condon, K; Jones, R
Abstract: The aim of this study was to describe two epizootics of high mortalities from infection with Streptococcus agalactiae, occurring in captive rays held in a marine display aquarium in south‐east Queensland, Australia, in 2009 and 2010. Five different species of rays were affected, including mangrove whiprays (Himantura granulata), estuary rays ( Dasyatis fluviorum), eastern shovelnose rays (Aptychotrema rostrata), white‐spotted eagle rays ( Aetobatus narinari) and blue‐spotted mask rays ( Neotrygon kuhlii) . This report describes the history of both epizootics including collection, quarantine and husbandry of rays, the disease epizootics, clinico‐pathological features of the disease, antimicrobial therapy, autogenous vaccine production, and laboratory studies including clinical and histopathology, bacteriology, PCR, molecular serotyping and sequencing of the bacterium S. agalactiae .